PENGARUH PROFITABILITAS, INTENSITAS ASET TETAP DAN INTENSITAS PERSEDIAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR BARANG KONSUMSI NON-SIKLIKAL TAHUN 2015 – 2020 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Trimides Christianto; Fharel M. Hutajulu; Emerald G. M Tobing (Fundamental Management Journal, 2023)
These studies is quantitative studies that aim to examining effect of profitabilities, capital intensities, and inventory intensities to Tax Avoidance. These studies take company list on non-cyclical customer good sectors on Indonesia Stock Exchanges at 2015 - 2020. Sample selections technique use Purposive Sampling techniques and obtain 156 researched data. Hypothesis test use Multipled Linear Regressions Analyst with a significances level of 5%. Result obtaine from these studies are base in partials tests, profitabilities, capital intensities, inventory intensities have a negative effect to tax avoidances. Keywords: profitability, capital intensity, inventory intensity, tax avoidance.